2018
DOI: 10.1007/s00784-018-2569-9
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between stress, cytokines, and salivary cortisol in pregnant and non-pregnant women with gingivitis

Abstract: Psychosocial stress may increase the risk of periodontal disease by altering the behavioral and immune responses of the individual. Therefore, the levels of stress should be taken into consideration in order to increase the efficacy of periodontal therapy in pregnant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…Fiorini et al have reported that the levels of IL‐1β, IL‐6, and IL‐8 in GCF are associated with periodontal PD and bleeding on probing in pregnant women (Fiorini et al., 2012). Yarkac et al have shown that the GCF level of IL‐6 is significantly higher in pregnant women compared with non‐pregnant women (Yarkac et al., 2021). In this study, IL‐6 and TNF‐α, two typical pro‐inflammatory cytokines were measured in the GCF of women underwent progesterone intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Fiorini et al have reported that the levels of IL‐1β, IL‐6, and IL‐8 in GCF are associated with periodontal PD and bleeding on probing in pregnant women (Fiorini et al., 2012). Yarkac et al have shown that the GCF level of IL‐6 is significantly higher in pregnant women compared with non‐pregnant women (Yarkac et al., 2021). In this study, IL‐6 and TNF‐α, two typical pro‐inflammatory cytokines were measured in the GCF of women underwent progesterone intervention.…”
Section: Discussionmentioning
confidence: 99%
“…O estresse é um mecanismo biológico caracterizado pela ativação imediata do sistema nervoso simpático e aumento da secreção de adrenalina, seguido da ativação do eixo hipotálamo-hipófise-adrenal e consequente elevação dos níveis de cortisol. (26) A medição dos níveis de cortisol na saliva está ganhando cada vez mais ampla aceitação como método diagnóstico porque eles correspondem apenas a fração bioativa do hormônio, podendo serem avaliados sob várias condições cognitivas e na presença de estresse e ansiedade. (27) Assim, a Terapia Floral, enquanto processo facilitador do autodesenvolvimento do ser humano, gera frequentemente a sensação de relaxamento ou de liberação do excesso de energia disfuncional com consequente redução do estresse.…”
Section: Discussionunclassified
“…To estimate the sample size for the current study, a statistical power analysis which was calculated using cortisol levels based on a study conducted by Yarkac et al (27) was performed by using a software (G * Power version 3.1.7, Franz Faul, Kiel, Germany). A total of 60 individuals was estimated to be enough to find a significant difference in cortisol levels (0.50 effect size at an α = 0.05 significance level, actual power = 0.9677, non-centrality parameter = 15.00, critical F = 4.01, numerator df = 1, dominator df = 58).…”
Section: Discussionmentioning
confidence: 99%